The Strategy Development of Batik Business in Kampung Batik, Semarang City - Baiti, Wakhidatun Nur; Widodo, Joko; Oktarina, Nina (Universitas Negeri Semarang, 2024)
One of the leading business sectors in Central Java is the textile and garment industry, particularly batik, which is predominantly managed by SMEs (small and medium enterprises). Batik is an artistic cultural heritage of Indonesia, admired worldwide, and deserving of preservation and cultivation to its fullest potential. Semarang City is famous for Semarangan batik, which features motifs that distinctly represent various corners of the city. However, Semarangan Batik is not yet widely recognized by the general public. The purpose of this research is to analyze the business development strategies for batik in the Kampung Batik of Semarang City. The research method used is descriptive-qualitative. The variables in this study include internal factors such as human resources, raw materials, marketing, and management, as well as external factors such as competition, socioeconomic conditions, and government support. The subjects of this research are batik artisans in the Kampung Batik of Rejomulyo Village, East Semarang District. The data analysis techniques used are descriptive analysis and SWOT analysis. The research results show that the IE matrix of the batik business in Kampung Batik of Semarang City is in cell V, indicating that the business is in a stable condition. The development strategies that can be implemented include product differentiation, marketing, and human resources. The findings of this research are expected to provide appropriate strategies for the development of the batik business in the Kampung Batik of Semarang City.